Who cloned the President? - Roy, Ron, 1940-; Woodruff, Liza (New York, NY : Scholastic Inc., 2004)
KC discovers that the President of the United States has been replaced by a clone and sets out with her friend Marshall on a dangerous mission to set things right.
G2
Keywords: Cloning -- Fiction